Nitrogen and sulfur effects on hard winter wheat quality and asparagine concentration. (May 2020) - Wilson, Tara L.; Guttieri, Mary J.; Nelson, Nathan O.; Fritz, Allan; Tilley, Michael
Abstract: Grain protein concentration and composition are key factors affecting winter wheat quality and are influenced by wheat genotype, available fertility, and growing conditions. These same parameters can affect free asparagine concentration in grain, and elevated asparagine can lead to acrylamide production in baked food products, which can be a health concern. The objectives of this study were to determine the effect of genotype, nitrogen (N), and sulfur (S) fertility on protein concentration, protein quality, dough rheology, and asparagine concentration in winter wheat grown on S-deficient soils. Treatments were arranged in a 3 × 2 × 4 factorial design in 2017 and 3 × 2 × 5 factorial design in 2018. There were three levels of N (56, 101 and 146 kg ha −1 ), two levels of S (0 and 22 kg ha −1 ), four levels of genotype in 2017, and five levels of genotype in 2018. Protein composition was evaluated as the percent polymeric protein using size exclusion high performance liquid chromatography. In both years, the ratio of polymeric to monomeric protein was increased by sulfur fertilization. Solvent retention capacity (SRC) was evaluated using the whole grain lactic acid-sodium dodecyl sulfate test. In 2018, S application increased the SRC by 217%–308%. However, in 2017, SRC improvement was limited to two genotypes and was modest, likely a consequence of the reduced protein concentration in S-treated plots. Free asparagine concentration averaged 9.8 μmol/g and 20.9 μmol/g in 2017 and 2018, respectively. Asparagine concentration in grain was affected by N, S, genotype, and their interactions. Sulfur application substantially reduced asparagine concentrations in both years. Dough rheology was evaluated in the 2018 trial using the farinograph test. Sulfur application increased average farinograph stability from 9.2 min to 14.6 min. Farinograph stability was effectively predicted by the SRC test (R 2  = 0.78). These results demonstrate the importance of ensuring adequate S fertility in winter wheat production. Graphical abstract: Image 1 Highlights: Sulfur application decreased asparagine concentration. Sulfur application increased lactic acid- SDS SRC values. Sulfur application increased the ratio of total polymeric protein concentration to total monomeric protein. Lactic acid- SDS SRC is a good predictor of farinograph stability. Sulfur application may beimportant to increase yield and quality of winter wheatgrown on sulfur-deficient soils.